Про деякі аспекти забезпечення в Україні права засуджених до позбавлення волі на охорону здоров’я - Колб, O.; Колб, І.; Kolb, A.; Kolb, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті здійснено аналіз нормативно-правових актів та стану лікувально-профілактичної й санітарно- протиепідемічної діяльності, що здійснюється в установах виконання покарань України та спрямована на забезпечення права засуджених до позбавлення волі на охорону здоров’я. The article is devoted to the analysis of legal acts and condition of medical and sanitary epidemiological activities in the penal institutions of Ukraine, which is aimed to ensure the rights of convicts to protect their health. The need to bring penal enforcement legislation of Ukraine in accordance with European standards is proven. Thus it is necessary to observe the requirements and rules of construction of the legal norms, such as: the presentation of norms in the articles of the legal act, the accordance of the adopted legal norms with articles of the Criminal Executive Code of Ukraine, peculiarities of the penal enforcement relations; the comparative approach to the formation of legal norms, the possibility of financing penitentiaries from the State Budget of Ukraine.
About Some Aspects of the Ensuring the Right to Health Care of Convicted Persons in Ukraine
Keywords: право засуджених на охорону здоров’я; засуджений до позбавлення волі; установа виконання покарань; лікувально-профілактична та санітарно-протиепідемічна робота; the right to health care of convicts; convicted to imprisonment; penal institutions; medical and sanitary epidemiological activities